MODELING AND IMPLEMENTATION OF AN ECO-OPTIMIZED NETWORK BASED ON VLANS FOR THE REDUCTION OF CARBON FOOTPRINTS - Bopatriciat Boluma Mangata; Evariste Sindani Mbuta; Patience Ryan Tebua Tene; Blanchard Kangulumba Mutanga (Bakti Nusantara Institute, 2022)
The present work proposes a model of responsible digitalization in the Democratic Republic of Congo, by implementing an eco-optimized network based on VLANs while reducing the carbon footprint, the technologies to be adopted and the energy and ecological efficiency measurement indicators to minimize the greenhouse gas emissions in DRC. The goals of such an architecture are to simplify the infrastructure, increase virtualization, save hardware and software, rationalize the use of the information system, reduce energy consumption and finally reduce the carbon footprint of the information system. With regard to the design of an optimal local network within the Directorate General of Taxes (DGI), we opted to set up a virtual local network (VLAN) that will be adapted to all DGI services. The architecture for the implementation of the optimal network within the DGI is composed of the following elements Seven VLANs for the Central Directorates; One VLAN for the operational services; One core switch (Cisco manageable switch), which enabled us to manage our network; One router with firewall for managing inter-VLAN traffic, and incoming and outgoing traffic for Internet access; Eight distribution switches that can connect equipment in the same VLAN.